THE COMPLEX NATURE OF AUTONOMY - PAIVA, Vera Lúcia Menezes de Oliveira e; BRAGA, Junia de Carvalho Fidelis (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
Drawing on Complexity Theory and on the literature of autonomy, the discussions herein presented will center around the language learner process of autonomy as a complex system. As empirical evidence to defend our assumptions, a corpus of 80 English language learning narratives, collected in Brazil, were examined and interwined with the theoretical discussion.